An Efficient Approach for Lithium and Aluminum Recovery from Coal Fly Ash by Pre-Desilication and Intensified Acid Leaching Processes - Shenyong Li; Shenjun Qin; Lianwei Kang; Jianjun Liu; Jing Wang; Yanheng Li (Metals, 2017)
A novel technique was developed for the recovery of lithium and aluminum from coal fly ash using a combination of pre-desilication and an intensified acid leaching process. The main components of the high-aluminum fly ash were found to be Al2O3 and SiO2, and the Al/Si ratio increased from 1.0 to 1.5 after desiliconization. The lithium content of the coal fly ash met national recycling standards. The optimal acid leaching conditions, under which the leaching efficiencies of lithium and aluminum were 82.23% and 76.72%, respectively, were as follows: 6 mol/L HCl, 1:20 solid to liquid ratio, 120 °C and 4 h. During the hydrochloric acid pressure leaching process, spherical particles of desilicated fly ash were decomposed into flakes. Part of the mullite phase was dissolved, and most of the glass phase leached into the liquor. The generation of the silicates hindered lithium transport, which decreased the leaching rate of lithium. This work suggests that the preprocessing is a promising option for effective recovery of high-aluminum and fly ash-associated lithium.